Macrofauna spatial differences within clam dredge-tracks and their implications for short-term fishing effect studies - Chícharo, Luís (2013)
In situ observations of clam dredging showed that the effects of the dredge on the benthic macrofauna may not be constant during a tow. A sand buffer forms in front of the gear approximately 10m after the beginning of a tow, and this pushes the sediment partially aside.In this study, we analyse differences in abundance, the number of taxa present, diversity, and evenness within sections of dredge-tracks in a disturbed, fished area and a non-fished area along the southern coast of Portugal. These areas were sampled by divers before and after dredge-fishing activity. At each site, three dredge-tracks were produced. These tracks were divided in three longitudinal sections 1start, middle and end) and two transverse sections 1track and edge). Six quadrats were used to sample macrofauna in each section of every track and edge. Our results show differences exist in macro- faunal distribution and abundance across sections of a dredge-track. These differences should be considered in any assessment of the short-term ecological impact of dredges on benthic macrofauna